Modelling Preservice Science Teachers' Environment-Friendly Behaviours - Ucar, Murat Berat; Canpolat, Erdal (Edith Cowan Univ, 2019)
The purpose of this study was to examine the relationships among the preservice science teachers' proenvironmental behaviours, environmental identity, and ecocentric and anthropocentric attitudes toward environment. A total of 576 (407 females and 169 males) preservice science teachers enrolling in five public universities' education faculties in Eastern and South-eastern Anatolian Region of Turkey were administered a questionnaire regarding the variables. Convenience sampling method was chosen to constitute the sample of this study. In order to analyse the data collected, descriptive statistics and path analysis as inferential statistics were utilized. According to the results of the study, preservice science teachers held moderate level of favourable environmental behaviours, had strong environmental identity, and possessed high level of ecocentric and moderate level of anthropocentric attitudes toward environment. Moreover, environmental identity directly and strongly predicted the preservice science teachers' proenvironmental behaviours. The findings revealed that environmental identity plays a crucial role in predicting proenvironmental behaviours.
Keywords: Gender-Differences; Attitudes; Identity; Values; Intentions; Emissions